Cuprous Oxide/Nitrogen-doped Graphene Nanocomposites as Electrochemical Sensors for Ofloxacin Determination - Wu, Fanghui; Xu, Fan; Chen, Le; Jiang, Binbin; Sun, Wenbin; Wei, Xianwen (Chemical research in Chinese universities, 2016)
Cu2O/nitrogen-doped grapheme（NG） nanocomposite material was prepared via a facile one step chemical reduction and characterized by means of X-ray diffraction（XRD） and scanning electron microscopy（SEM）. A new electrochemical sensor was then fabricated by coating Cu2O/nitrogen-doped graphene nanocomposite with Nation on glassy carbon electrode（Cu2O/NG/Nation/GCE）. The electrochemical response of this modified electrode toward of- loxacin was examined by cyclic voltammetry. The results indicate that Cu2O/NG/Nafion composite-modified elec- trode exhibits higher catalytic activity in the electrochemical oxidation of ofloxacin compared with glassy carbon electrode（GCE）, Cu2O/Nafion modified electrode（Cu2O/Nafion/GCE）, and N-doped graphene/Nation modified electrode（NG/Nafion/GCE）. Under optimal conditions, the peak current was found to be linearly proportional to the concentration of ofloxacin in the 0.5-27.5 μmol/L and 27.5-280 μmol/L ranges with a lower detection limit of 0.34 μmol/L, higher sensitivity of 39.32 μA-L-mmoV1 and a shorter reaction time of less than 2 s. In addition, Nation can enhance the stability of the modified electrode and prevent some negative species. Thus the modified electrode exhibits good selectivity and a long working life. The Cu2O/NG/Nafion composite modified electrode shows promising application in electrochemical sensors, biosensors, and other related fields because of its excellent properties.